Coumarin as a green inhibitor of chloride-induced aluminum corrosion: theoretical calculation and experimental exploration. Issue 40 (16th July 2021) - Tang, Huajie; Sun, Jianlin; Su, Daoxin; Huang, Ying; Wu, Ping
Abstract : The corrosion inhibition mechanism of coumarin in a chloride-containing environment. Abstract : In the present work, the adsorption mechanism and corrosion inhibition effect of coumarin as a green inhibitor was characterized. Quantum chemical calculation and molecular dynamics simulation of the coumarin molecule were performed to get insight into the adsorption model by assessing the frontier orbital parameters and adsorption configuration. The theoretical calculation disclosed that coumarin exhibited a higher adsorption reactivity in the water phase than that in the gas phase, and the CO structure in coumarin was the most favorable site for adsorption occurring. Coumarin could adsorb spontaneously on an aluminum surface in a parallel manner, where electron donation occurred from the aluminum surface to the inhibitor. Additionally, the experimental investigation determined that coumarin decreased the aluminum dissolution by suppressing both the anodic and cathodic reactions. The optimal coumarin concentration of 0.5 wt% resulted in a maximum inhibition efficiency (89.6%), but coumarin at a higher concentration would lead to the competitive and unstable adsorption of inhibitor molecules, thus decreasing the inhibition effect. Moreover, surface chemical characterization confirmed the formation of Al–coumarin complexes, which was in accordance with the theoretical calculation.